2013
DOI: 10.2298/vsp1307690p
|View full text |Cite
|
Sign up to set email alerts
|

Acute meningoencephalitis in a patient with systemic lupus erythematosus

Abstract: This case alerts to the need of careful examination of patients with SLE, collection of adequate cultures and evaluation of predisposition towards infections, before the introduction of immunosuppressants due to potentially fatal infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…4,5 Central nervous system (CNS) infections are rare bacterial complications of SLE, but can be a significant cause of mortality. 6 Here, we report a case of Listeria monocytogenes-associated multiple brain abscesses in a patient with SLE.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…4,5 Central nervous system (CNS) infections are rare bacterial complications of SLE, but can be a significant cause of mortality. 6 Here, we report a case of Listeria monocytogenes-associated multiple brain abscesses in a patient with SLE.…”
mentioning
confidence: 90%
“…[8][9][10][11] To the best of our knowledge, since Dr Schulze et al 12 reported the first case of a patient with disseminated SLE who died due to L. monocytogenes infection in 1953, 52 cases have been reported in the English-language literature (Table 2). [4][5][6][7] Meningoencephalitis is the most common manifestation in patients with SLE who develop L. monocytogenes infections; other cases with neurolisteriosis. 9,34 As few as 6 cases have been reported, with 4 involving multiple brain abscesses (Table 3).…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
See 1 more Smart Citation